Membuat Blog dengan Wordpress dan Artikel Menggunakan Tools Artificial Intelligence - Juliantara. KW, Pande Putu Ode; Smrti, Ni Nyoman Emang; Andisana, I Putu Gd Sukenada; Atho'illah, Ibnu; Erlangga, Anak Agung Gde Wahyu Sukma; Dharayanti, Desak Made Pratiwi; Sutarjana, I Wayan (Universitas Pahlawan Tuanku Tambusai, 2026)
Based on a needs analysis of partners at SMK Negeri 1 Gianyar class XI, students experienced difficulties in learning to write blogs as a medium for marketing products. Although there are many blog service providers available, students have not been able to determine which blog platform is easy to use. The next difficulty is how to improve blog rankings on internet search engines. Through this training, students were provided with material on creating blogs using WordPress, writing articles relevant to search optimization needs, and utilizing Artificial Intelligence (AI) to help create appropriate content. The results of the activity showed an increase in students' knowledge regarding the creation and management of blogs with WordPress, an increase in their ability to compose articles relevant to supporting blog rankings on search engines, and their ability to utilize AI as a medium for creating marketing articles.